The Role of Planning in Management: Strategies to Achieve Organizational Success - Koppel Tavo; Romann Rasmus (Sharia Oikonomia Law Journal, 2024)
This article aims to outline the importance of planning in the context of organizational management. Planning, both strategically and operationally, is explained as a crucial foundation for achieving organizational goals. The data collection method used is the literature method, which is used to trace historical and theoretical data related to planning in management. Strategic planning, as a comprehensive long-term plan, is considered the foundation for operational planning in achieving organizational goals. Three main reasons why strategic planning is important: first, as a basic framework for all types of planning; second, it facilitates the understanding of other planning; Third, as a starting point for evaluating managerial and organizational activities as a whole.